Evaluasi Sistem Proteksi Kebakaran Aktif pada Gedung Administrasi Perusahan Listrik Surabaya - Senna Malik Ibrahim; Jundan Ahsana Muhammad; Kholis Widodo; Mochammad Luqman Ashari (Journal of Student Research, 2025)
Fire is one of the serious threats to buildings, especially national vital objects such as Building B Administration Electric Company East Java. Evaluation of the fire protection system, which includes Portable Fire Extinguishers (APAR), hydrant systems, and Fire Alarm Systems (FAS), is important to ensure the readiness and suitability of the devices in dealing with potential fires. This study was conducted through direct observation and comparing the results with international safety standards such as NFPA 10, NFPA 14, and NFPA 72. The evaluation results showed that the level of suitability of APAR was 89%, the hydrant system 72.6%, and FAS 83.66%. Although most elements of the fire protection system have met the standards, improvements are needed, especially in hydrant accessibility, APAR maintenance, and the implementation of fire alarm simulations. This evaluation provides important input to improve operational security and safety at Building B Administration Electric Company East Java..